Design and Optimization of Hybrid Photovoltaic /Diesel Storage Battery Mini-Grid System for Rural Electrification (Case Study, Albasa Village in Benshangul Gumuz Region, Ethiopia) - Amare, Gebermedhin (ASTU, 2021)
Renewable energies are increasingly seen as the best solution to a growing global population demanding affordable access to electricity while reducing the need for fossil fuels. Country of Ethiopia has vast untapped solar, wind, geothermal, and hydroelectric sources that hold the potential to meet domestic needs. In this thesis, solar PV/Diesel Generator/battery bank/ converter have been simulated and optimized for the rural area of Albasa village among the woreda of Dibate/Metekel Zone in Benshangul Gumuz region of Ethiopia. The optimization software used for this paper is HOMER it determines the optimal architecture. And energy management system is the programmable logic controller (PLC) as a control strategy of the hybrid system. In this applications at remote village with 1110 households with average of five family members per household. Based on the design of hybrid system Primary load demand of the village was 279kWh/day, peak load of 67kW, deferrable energy is about 29kWh/day, and deferrable peak load of 1.9kW were involved during optimization of the power system. Solar PV was considered as primary sources to supply electricity directly to the load and to charge battery bank when there were excess energy generation. However, either in peak load times or low generation of primary sources storage battery bank discharged and Diesel Generator could also be used as a source. The load has been suggested for residential loads and deferrable load (water pumping). During design of this power system set-up, the optimization was done based on the load demand, climatic data, economics of integrated system components and other parameters in which the total NPC and levelized COE have to be minimized to select economically feasible and technically capable hybrid power system. Furthermore; a programmable logic controller (PLC) modeling is also modeled to compare the possible potentials available (only solar energy, only diesel generator or hybrid energy) and take a decision. The decision of programmable logic controller (PLC) modeling is based on the instructional rules written on it.
Keywords: Mini-Grid Hybrid System, Rural Electrification, PV, Diesel Generator, Battery Bank, Primary Load, Deferrable Load, HOMER, Programmable Logic Controller (PLC)